Possible Impact of Wide-scale Vaccination Against Serogroup B Neisseria Meningitidis on Gonorrhea Incidence Rates in One Region of Quebec, Canada. (4th October 2017) - Longtin, Jean; Dion, Rejean; Simard, Marc; Betala Belinga, Jean-Francois; Longtin, Yves; Lefebvre, Brigitte; Labbé, Annie-Claude; Deceuninck, Genevieve; De Wals, Philippe
Abstract: Background: Owing to a persistent increase of serogroup B Neisseria meningitidis (Nm) invasive infections in the Saguenay-Lac-Saint-Jean (SLSJ) region of the province of Quebec (Canada) since 2006, a wide-scale vaccination campaign of individuals aged 6 months to 20 years was conducted between May and December 2014 using the 4-component protein-based meningococcus serogroup B vaccine (4CMenB). Components of this vaccine have shown to potentially cross-react with Neisseria gonorrhoeae (Ng). The study objective was to assess the impact of the vaccination campaign on Ng incidence rate (IR). Methods: Ng cases notified to public health authorities during prevaccination period (January 2006 to June 2014) and postvaccination period (July 2014 to June 2017) were analyzed. The impact of this mass campaign was estimated by a Poisson regression model, including the year (11 July–June categories), age (14–20 vs. 21 years and older), and the intervention (0 by default and 1 in those 14–20 years in the period of July 2014 to June 2017). Results: Overall vaccine coverage was 82% in the target group. A total of 231 Ng cases were reported among persons 14 years and older (IR: 8.4/100, 000 person-years) of the SLSJ region from January 2006 to June 2017. A decrease in the Ng number of cases and IR among individuals 14–20 years was observed during the post-vaccination period whereas it increased in those 21 years and older (figure). Estimate of vaccination impact was an Ng risk reduction of 59% (95% CI: −22% to 84%; P  = 0.1). During the same period, Chlamydia trachomatis (Ct) infections increased among persons of both age groups in the SLSJ region. Conclusion: Although the estimate of the impact of the campaign was not statistically significant, possibly due to limited size of the study population and the low incidence of the disease, it is congruent with results of a case–control study in New Zealand showing an OMV-MeNZB vaccine effectiveness of 31%. A higher effectiveness of 4CMenB is a plausible hypothesis as three additional proteins also found in Ng are included in the vaccine used in the SLSJ region. The results of this ecologic study suggest cross-protection of 4CMenB vaccine against Ng infections. Further studies on this topic are warranted. Disclosures: P. De Wals, GlaxoSmithKline: Grant Investigator and Scientific Advisor, Grant recipient and travel expenses. Pfizer: Grant Investigator and Scientific Advisor, Grant recipient and travel expenses. Sanofi-Pasteur: Grant Investigator and Scientific Advisor, Grant recipient and travel expenses. Novartis: Grant Investigator and Scientific Advisor, Grant recipient and travel expenses.